Risk events in sheep rarming in Bulgaria - Hristina Harizanova; Tsvetana Harizanova Bartos; Nikola Metodiev Metodieva (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 12th Edition, 2021)
The aim of the research was to find some of the most often occurred risk events in sheep farms in Bulgaria. 22 sheep farms in Bulgaria were surveyed and questionnaire information was collected from them in 2020.As a result of the study, it was found that the number of farms in which a risk event had occurred in the last 5 years was almost equal to the number of farms in which such an event had not occurred. Of the climatic risks, the most common were drought, followed by hail and cold. Of the other risks, the most common were the sale of products below cost and infectious animal diseases. In the case of a risk event, the effect on the activity of the farm was usually from no effect to medium. As measures to deal with the risk event, the farmers responded differently: some of them financed their activity from another business; others were looking for better markets for their products; some coped at the expense of family deprivation, or waited for the risk event to pass. Also, some farmers had started vaccinating animals against diseases. The majority of farmers did not receive compensation from the state in the case of a risk event. Only 9% of farmers had insurance other than that required for machinery. The prevailing part of the farmers believed that the state did not adequately support them in terms of risk.
Keywords: Q10; Q12; 330; sheep farming; risk factors; farm insurances